2008
DOI: 10.1158/0008-5472.can-07-2997
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Src Family Kinases Inhibits Growth and Lymph Node Metastases of Prostate Cancer in an Orthotopic Nude Mouse Model

Abstract: Aberrant expression and/or activity of members of the Src family of nonreceptor protein tyrosine kinases (SFK) are commonly observed in progressive stages of human tumors. In prostate cancer, two SFKs (Src and Lyn) have been specifically implicated in tumor growth and progression. However, there are no data in preclinical models demonstrating potential efficacy of Src inhibitors against prostate cancer growth and/ or metastasis. In this study, we used the small molecule SFK/ Abl kinase inhibitor dasatinib, cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
206
2
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(222 citation statements)
references
References 44 publications
13
206
2
1
Order By: Relevance
“…This point is critical to our in vivo studies as it allows for PSA levels to be used as a surrogate marker for tumour growth in bone in response to this therapy. Also of interest, despite recent literature demonstrating the importance of the SFK member, lyn, in regulating proliferation of PC-3 CaP cells (Park et al, 2008); we show that lyn phosphorylation is unaffected in C4-2B cells on treatment with dasatinib. Thus implying that lyn inactivation is not involved in the inhibition of proliferation by dasatinib in these cells.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This point is critical to our in vivo studies as it allows for PSA levels to be used as a surrogate marker for tumour growth in bone in response to this therapy. Also of interest, despite recent literature demonstrating the importance of the SFK member, lyn, in regulating proliferation of PC-3 CaP cells (Park et al, 2008); we show that lyn phosphorylation is unaffected in C4-2B cells on treatment with dasatinib. Thus implying that lyn inactivation is not involved in the inhibition of proliferation by dasatinib in these cells.…”
Section: Discussionmentioning
confidence: 63%
“…It has been previously reported that lyn has a prominent role in the control of proliferation of PC-3 CaP cells in vitro whereas src played a more significant role as a mediator of migration (Park et al, 2008). Therefore in our subsequent experiments, we investigated the effects of dasatinib on phosphorylation of lyn and src, specifically, in C4-2B cells.…”
Section: In Vitro Effects Of Dasatinib On C4-2b Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, we treated animals with a dose [30 mg/(kg day)] higher than that utilized in CML pre-clinical models 19 and in other solid tumours. 33 In addition, HTLA-230 tumours were vascularized and Dasatinib treatment did not induce any significant change, at least as assessed by microscopic observation. Using SY5Y cells in vivo in the orthotopic model, we failed to demonstrate Dasatinib antitumour activity at 30 mg/(kg day) and at 60 mg/(kg day) when starting treatment 7 days after transplantation.…”
Section: Discussionmentioning
confidence: 91%
“…14,15 Studies have shown that dasatinib specifically interrupts cell motility in other forms of cancer including prostate, melanoma, and Ewing sarcoma. [16][17][18][19] It is likely that a similar process occurs in CML cells; a subject currently under investigation. Whilst these cells are resistant to apoptosis, dasatinib does exert a significant inhibitory effect upon 5 cell motility by blocking src kinase mediated activity.…”
mentioning
confidence: 99%